Analysis of Working Postures on the Low Back Pain Incidence in Traditional Songket Weaving Craftsmen in Ketang Manggarai Village, NTT - Yuliana Suryati; Bonavantura Nursi Nggarang (Journal of Epidemiology and Public Health, 2020)
Background: Low back pain (LBP) is pain that is experienced in between the corners of the lower ribs to the fold of the lower buttocks, namely the lumbar-sacral area and is often accompanied by pain radiations to the legs and feet. LBP is caused by sitting for a long time in a monotonous position, causing tension on back muscles and can lead to the surrounding soft tissue damage. Traditional cloth weavers are at risk of LBP due to their activities that requiring sitting and bending positions, in a same certain position and for a long time. Analysis of appro-priate working posture can be a reference to reduce the risk of LBP. This study aims to determine working posture and its effect on the incidence of LBP and the risk level of each work attitude element of the woven fabric manufacturing activity.Subjects and Method: This was a quantitative study using a retrospective study. The subjects of this study were 40 weavers of traditional fabrics. The dependent variable was working posture. The independent variable was low back pain (LBP). LBP pain measured using the numeric rating scale (NRS) and the Quick Exposure Check (QEC) questionnaire to determine working posture. Results: There was a significant relationship between LBP and working posture (QEC level) (OR= 0.15; 95% CI= 0.03 to 0.71; p= 0.017), age (OR= 5.64; 95% CI= 1.07 to 2.96; p= 0.001), and tenure OR= 0.44; 95% CI= 0.16 to 0.85; p= 0.014). Age and tenure (hours) also influence the incidence of LBP.Conclusion: Age, working experience (length of work), and working posture have a high contribution to the incidence of Low back pain. The results of this study expected to be a reference of comfortable working posture for workers and efforts to prevent and manage low back pain.Keywords: working posture, low back painCorrespondence: Yuliana Suryati. Faculty of Health Science, Uni-versitas Katolik Indonesia Santu Paulus Ru-teng. Jl. Ahmad Yani 10 Manggarai, East Nusa Tenggara. Email: syulty12@gmail.com. Mobile: 081328430358.Journal of Epidemiology and Public Health (2020), 05(04): 469-476https://doi.org/10.26911/jepublichealth.2020.05.04.09